Evidence for exercise-related plasticity in functional and structural neural network connectivity. (December 2021) - Won, Junyeon; Callow, Daniel D.; Pena, Gabriel S.; Gogniat, Marissa A.; Kommula, Yash; Arnold-Nedimala, Naomi A.; Jordan, Leslie S.; Smith, J. Carson
Highlights: Regular participation in exercise and higher fitness modulate functional connectivity of the brain. Exercise-related changes in functional connectivity corresponds to cognitive and motor performances improvements. Greater physical activity levels and fitness are associated with better motor and cognitive function, mediated by enhanced white matter microstructural integrity. Abstract: The number of studies investigating exercise and cardiorespiratory fitness (CRF)-related changes in the functional and structural organization of brain networks continues to rise. Functional and structural connectivity are critical biomarkers for brain health and many exercise-related benefits on the brain are better represented by network dynamics. Here, we reviewed the neuroimaging literature to better understand how exercise or CRF may facilitate and maintain the efficiency and integrity of functional and structural aspects of brain networks in both younger and older adults. Converging evidence suggests that increased exercise performance and CRF modulate functional connectivity of the brain in a way that corresponds to behavioral changes such as cognitive and motor performance improvements. Similarly, greater physical activity levels and CRF are associated with better cognitive and motor function, which may be brought about by enhanced structural network integrity. This review will provide a comprehensive understanding of trends in exercise-network studies as well as future directions based on the gaps in knowledge that are currently present in the literature.